Identifikasi pH Larutan Antosianin Kol Merah (Brassica Oleracea Var.) terhadap Kinerja Prototipe Dye Sensitized Solar Cell (DSSC): Ferri Rusady Saputra, Suryasatriya Trihandaru, Adita Sutresno - Ferri Rusady Saputra, Ferri Rusady Saputra; Suryasatriya Trihandaru, Suryasatriya Trihandaru; Adita Sutresno, Adita Sutresno (Jurnal Fisika dan Aplikasinya, 2025)
Red cabbage is one of the organic materials containing anthocyanin. Anthocyanin can be used as the dye in Dye sensitized Solar Cell (DSSC) prototype manufacture as the electron donor. In this study, the solar cell was immersed in the extract solution of red cabbage (Brassica oleracea Var) with pH varying at pH 1.5, pH 2.5, and pH 3.5. The measurement results showed that the solar cell with red cabbage anthocyanin soaking solution at pH of 3.5 and the best result as at the open circuit is obtained 56 uA of short circuit (Isc), at the open voltage (Voc) is obtained 250 mV and 24.89 uA/cm2 of current density in the 15 mm × 15 mm area. The conversion efficiency value of solar cell reached 2.55 × 10-3 %